(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1862)
The author reports on the excavation of a cairn found on Cairn Conan, near St Vigeans. He includes some local history, the dimensions of the cairn and the process of the excavation. It is noted that the excavation has not been finished, but the author suggests some underground chambers that he believes may be of a similar style and speculates about what the discoveries in this area could mean for the wider study of cairns in the UK.